LANGUAGE POLICY AND METHODOLOGY - Liddicoat, Antony J. (International Journal of English Studies, 2009)
The implementation of a language policy is crucially associated with questions of methodology. This paper explores approaches to language policy, approaches to methodology and the impact that these have on language teaching practice. Language policies can influence decisions about teaching methodologies either directly, by making explicit recommendations about the methods to be used in classroom practice, or indirectly, through the conceptualisation of language leaming which underlies the policy. It can be argued that all language policies have the potential to influence teaching methodologies indirectly and that those policies which have explicit recommendations about methodology are actually functioning of two levels. This allows for the possibility of conflict between the direct and indirect dimensions of the policy which results from an inconsistency between the explicitly recommended methodology and the underlying conceptualisation of language teaching and learning which informs the policy.